MSH3-deficiency initiates EMAST without oncogenic transformation of human colon epithelial cells. - Christoph Campregher (Public Library of Science (PLoS), 2012)
Background/aim Elevated microsatellite instability at selected tetranucleotide repeats (EMAST) is a genetic signature in certain cases of sporadic colorectal cancer and has been linked to MSH3-deficiency. It is currently controversial whether EMAST is associated with oncogenic properties in humans, specifically as cancer development in Msh3-deficient mice is not enhanced. However, a mutator phenotype is different between species as the genetic positions of repetitive sequences are not conserved. Here we studied the molecular effects of human MSH3-deficiency. Methods HCT116 and HCT116+chr3 (both MSH3-deficient) and primary human colon epithelial cells (HCEC, MSH3-wildtype) were stably transfected with an EGFP-based reporter plasmid for the detection of frameshift mutations within an [AAAG]17 repeat. MSH3 was silenced by shRNA and changes in protein expression were analyzed by shotgun proteomics. Colony forming assay was used to determine oncogenic transformation and double strand breaks (DSBs) were assessed by Comet assay. Results Despite differential MLH1 expression, both HCT116 and HCT116+chr3 cells displayed comparable high mutation rates (about 4×10(-4)) at [AAAG]17 repeats. Silencing of MSH3 in HCECs leads to a remarkable increased frameshift mutations in [AAAG]17 repeats whereas [CA]13 repeats were less affected. Upon MSH3-silencing, significant changes in the expression of 202 proteins were detected. Pathway analysis revealed overexpression of proteins involved in double strand break repair (MRE11 and RAD50), apoptosis, L1 recycling, and repression of proteins involved in metabolism, tRNA aminoacylation, and gene expression. MSH3-silencing did not induce oncogenic transformation and DSBs increased 2-fold. Conclusions MSH3-deficiency in human colon epithelial cells results in EMAST, formation of DSBs and significant changes of the proteome but lacks oncogenic transformation. Thus, MSH3-deficiency alone is unlikely to drive human colon carcinogenesis.